Crescimento e fixação biológica do nitrogênio em soja cultivada com doses de lodo de esgoto compostado - Lobo, Thomaz Figueiredo [UNESP]; Grassi Filho, Hélio [UNESP]; Bran Nogueira Cardoso, Elke Jurandy; Almeida, Leandro de Souza [UNESP]; Nomiyama Junior, Norio [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The use of sewage sludge is a highly promising practice for the development of sustainable agricultural systems. The objective of this study was to evaluate doses of sewage sludge composted with and without Rhizobium inoculation in leaf N content, nodule number, nodule dry weight and plant during flowering. The experiment was conducted in the greenhouse of the Department of Soil Science and Natural Resources College of Agricultural Sciences of Botucatu, using as substrate used in vessels of 30 liters a Red Yelow Latosol sandy texture with experimental design adopted was randomized blocks constituted for 10 treatments and five doses of composted sewage sludge (0, 10, 20, 30, 40 t ha(-1)) with or without inoculation Bradyrhizobium japonic with three replications. There was an increase in the number and dry weight of nodules and shoot dry mass of soybeans due to the increase of the dose of sludge up to a dose of 20 t ha(-1) and after this dose there was a decrease of these parameters. At a dose of 10 t ha(-1) sludge compost inoculated seeds showed higher for foliar concentrations of N and number of nodules compared with uninoculated seeds. At a dose of 30 t ha(-1) inoculated seeds were higher compared to uninoculated in all parameters.
Growth and nitrogen fixation in soybean treated with doses of composted sewage sludge
Keywords: Microbiology of soil; biosolids; rhizobium; sustainability